Paddy-tech machines / Awangku Irfan Haqimie Awang Abdul Ghani, Sailfan Sultan and Muhammad Afiq Afdhal Abdua - Awang Abdul Ghani, Awangku Irfan Haqimie; Sultan, Sailfan; Abdua, Muhammad Afiq Afdhal (Faculty of Plantation and Agrotechnology, 2023)
Rice and paddy, Malaysia's two most important food crops, are at the center of the country's efforts to achieve food self-sufficiency. Why is rice considered to be the most valuable food crop in Malaysia? Rice is the primary source of caloric intake for most people. Paddy agriculture is the primary source of income for forty percent of the country's farmers. The regulations governing paddy and rice in Malaysia are intended to provide a steady price for farmers, a consistent profit margin for business owners, and a consistent supply of rice for the general public. The purpose of this study is to persuade rice farmers to adopt our product, which has a number of benefits that paddy plantation users may take advantage of. In the process of milling the rice after harvest, our method not only makes husking simpler, but it also makes the milling process simpler. As part of our program, cutting-edge equipment will be provided to Malaysian farmers so they may better expand the paddy business. Processing of the paddy after harvest is aided by this. A robust fuselage, a safety protection system, an expansion hopper, and a 220kilowatt power machine are all included in our product.